Translation and feminism in post-Islamic revolution Iran: A sociological approach. Issue 3 (3rd July 2021) - Jalalian Daghigh, Ali; Kenevisi, Mohammad Sadegh; Mohd Jan, Jariah
Abstract: With the 1979 Islamic revolution in Iran, the pre-revolution secular modernisation process was interrupted and, as believed by the liberal activists, the Islamisation of rules and domination of political Islamic views in the society imposed restrictions on Iranian women. This led specifically part of the urban, educated middle-class women to be inclined toward secular-oriented feminism in their struggle against inequalities. Inspired by Luhmann's social systems theory, the current study investigates the social function of translation in communicating feminist ideas in the environment and context of Iran. The study is conducted through a thematic analysis of summaries of domestic (locally authored) and translated books on women's rights published in post-revolutionary Iran. The differences in the ideas covered in the translated books compared to those in domestic books are discussed, demonstrating the unique role of translation as a communication medium in making external feminist ideas accessible to the Iranian people and disseminating them in the society, potentially contributing to the challenge against the official fundamentalist view and discourse on women's rights.